Uji Aktivitas Penyembuhan Luka Sayat Gel Ekstrak Etanol Lidah Buaya (Aloe Vera L.) pada Mencit Putih Jantan (Mus Musculus) - Yulia Asmindra Milasanti; Ratih Tyas Widara; Aldesra Fitri (Journal of Pharmaceutical and Health Research, 2023)
Aloe vera (Aloe vera L.) is an herbal plant that contains phytochemicals such as tannins, saponins, flavonoids, and polyphenols, which are useful in healing cut wounds. The phytochemical content has antimicrobial, antibacterial, and antiseptic properties. Several research findings show wound healing activity in experimental animals that have been treated with aloe vera plant extract. This research aimed to make ethanol extract gel from aloe vera leaves and test cuts on male white mice (Mus musculus). The type of research used is true experimental design research. An incision wound was made on the back of the mouse with a length of 1 cm and a depth of 2 mm. The test animals used were 24 animals which were divided into 6 experimental groups, namely Positive Control (Bioplacenton), Negative Control (Without extract content), Base (Without aloe vera extract and preservatives), F1 (Aloe vera extract content 2.5%), F2 (Aloe vera extract content 5%), and F3 (Aloe vera extract content 7.5%). Statistical analysis of wound healing data was carried out using the One way ANOVA (Analysis of Variants) method, while the physical examination of the gel formulation was described descriptively. The statistical test results significantly affected wound healing in male white mice (p<0.05). There is a significant difference between the negative control and F3, p-value = 0.027. The best activity in the wound healing process is F3, with an average percentage of wound healing on the 7th day, F2 on the 8th day, and F1 on the 9th day.